CURRENT ISSUES OF GIARDIASIS - Пришляк, О. Я.; Дикий, Б. М.; Кондрин, О. Є.; Процик, А. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
There are results of treatment of giardiasis different antiparasitic drugs are given in this article. The aim of the study was to investigate the clinical and laboratory tiberal efficiency compared with the use of metronidazole and furozalidonom. There was 32 patients for observation who were hospitalized in Ivano-Frankivsk Regional Clinical Hospital of Infectious Diseases. Patients were divided into 2 groups: patients of group 1 received as causal treatment metronidazole and furazolidone treatment, and patients in group 2 received tiberal. In the combined therapy include chelators, choleretic means probiotics. According to the investigation, patients frequently observed signs following syndromes: dyspeptic, intoxication and allergic what is response to the general trend of this disease. Symptoms such as fatigue, recurrent headaches, loss of appetite, abdominal pain disappeared an average of 2-3 days before for the treatment, where we using tiberal. Exanthema kept longer in patients of group 1. Repeated detection of Giardia was observed after treatment three times less for tiberal than in other antiprotozoal drugs. Given the results of this study can be concluded that high clinical and laboratory efficacy tiberal in the treatment of giardiasis. The drug has a wide spectrum antiprotozoal action, was well tolerated by all patients, side effects or intolerance to the drug in patients was not observed.